Pengembangan Instrumen Penilaian Tes Soal Pilihan Ganda Berbasis HOTS Pada Mata Pelajaran Administrasi Umum Jurusan OTKP SMK Negeri 1 Lamongan - Fia Maulidia; Triesninda Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The development of HOTS-based assessment instruments for general administration subjects aims to find out developing assessment instruments, quality of developing assessment instruments, and students' high-level thinking skills. This type of research is R&D, using the 4D development model with the stages of defining, designing, developing, and disseminating. This study only reached the development stage because the subject of this study was limited to class X OTKP SMK Negeri 1 Lamongan. The results showed that, material quality by material experts 100% (very strong), evaluation experts 89% (very strong), and linguists 62% (strong). 25 questions are valid and 5 questions are invalid, the reliability is 0.666 (high). Of the difficulty of the questions, 7 questions (23%) are easy, 22 questions (74%) are moderate, and 1 question (3%) is difficult. From the power of differentiation, 14 questions (47%) are very good, 12 questions (40%) are good, 3 questions (10%) are enough, and 1 question (3%) is not good. From the questioners, 20 questions (67%) had several functions and 10 questions (33%) all functioned, then 25 best questions were taken based on validity. Of the high-level thinking skills of students, 6 students (9%) are very good, 18 students (26%) are good, 45 students (64%) are sufficient, and 1 student (1%) is lacking.